Circulating fluidized bed combustion reactor: Computational Particle Fluid Dynamic model validation and gas feed position optimization. (2nd September 2016) - Thapa, R.K.; Frohner, A.; Tondl, G.; Pfeifer, C.; Halvorsen, B.M.
Highlights: Computational Particle Fluid Dynamic model is validated against experimental measurements in the cold flow model of a Circulating Fluidized Bed. Optimum ratio of primary air feed to total height of reactor is 0.125. Optimum ratio of secondary air feed to total height of reactor is 0.375. Bed material circulation rate is less at increasing temperature. Bed material circulation rate is less with combustion reactions. Abstract: A 3D Computational Particle Fluid Dynamic (CPFD) model is validated against experimental measurements in a lab-scale cold flow model of a Circulating Fluidized Bed (CFB). The model prediction of pressure along the riser, downcomer and siphon as well as bed material circulation rates agree well with experimental measurements. Primary and secondary air feed positions were simulated by varying the positions along the height of the reactor to get optimum bed material circulation rate. The optimal ratio of the height of primary and secondary air feed positions to the total height of the riser are 0.125 and 0.375 respectively. The model is simulated for high-temperature conditions and for reacting flow including combustion reactions. At the high temperature and reaction conditions, the bed material circulation rate is decreased with the corresponding decrease in pressure drop throughout the CFB for the given air feed rate.